Quantification of proteome changes in bovine muscle from two-dimensional electrophoresis data - Daniel Franco; Ariadna Mato; Francisco J. Salgado; María López-Pedrouso; Mónica Carrera; Susana Bravo; María Parrado; José M. Gallardo; Carlos Zapata (Data in Brief, 2015)
Proteome changes in the longissimus thoracis bovine muscle in response to pre-slaughter stress were assessed on the basis of two-dimensional electrophoresis (2-DE) data. In this study, the bootstrap resampling statistical technique and a new measure of relative change of the volume of 2-DE protein spots are shown to be more efficient than commonly used statistics to reliably quantify changes in protein abundance in stress response. The data are supplied in this article and are related to “Tackling proteome changes in the longissimus thoracis bovine muscle in response to pre-slaughter stress” by Franco et al. [1].